2022
DOI: 10.1108/emjb-01-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of corporate governance and corporate social responsibility on corporate performance: an Iberian panel data evidence

Abstract: PurposeThe main goal of this paper is to study the influence of some corporate governance, corporate social responsibility (CSR), and corporate-specific characteristics on the performance of Iberian-listed companies.Design/methodology/approachTo achieve the paper's aim, the authors have used data from 33 Portuguese-listed companies, and 60 Spanish-listed companies, for the period 2011 to 2018. To test the hypotheses, the authors employed the generalized method of moments (GMM) estimation method, developed by A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 115 publications
1
8
0
Order By: Relevance
“…The author affirmed that an increase in the debt level can lead to future underinvestment, as well as that the reduction in the company’s value turn ends up negatively influencing performance. The same results were achieved by Cai and Zhang (2011) and Neves et al (2022d) or Neves et al (2022c), corroborating H4 . This result revealed that debt continues to be an internal and external important factor, changing the risk potential financially and, therefore, may affect corporate performance.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The author affirmed that an increase in the debt level can lead to future underinvestment, as well as that the reduction in the company’s value turn ends up negatively influencing performance. The same results were achieved by Cai and Zhang (2011) and Neves et al (2022d) or Neves et al (2022c), corroborating H4 . This result revealed that debt continues to be an internal and external important factor, changing the risk potential financially and, therefore, may affect corporate performance.…”
Section: Resultssupporting
confidence: 84%
“…The company size has a negative relationship with the EBITTURNOVER (Model 2), corroborating H2 and the studies of Almus and Nerlinger (1999), Evans (1987a) and Hall (1987). This result showed that smaller companies need to reach a stage of minimum efficiency to survive in the market in which they operate (Neves et al , 2022d). On the other hand, Model 1 (ROA) verified that there is no relationship between the company’s size and performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was then supported by the findings of another study by Carvalho et al (2021), who also stated that CG has no impact on Tobin's Q. However, some research concluded a significant relationship between CG and Tobin's Q (Hossain, 2022;Neves et al, 2022).…”
Section: Tobin's Qmentioning
confidence: 66%